Interactive role of breast cancer on dyslipidemia and hypertension metabolic risk according to treatment exposure and menopausal status - Al-Zeidaneen Safaa A.; Ahmad Mousa N.; Al-Ebous Ali D.; Saudi Rawan MohD Al (Forum of Clinical Oncology)
Breast cancer (BC) is the principal cause of cancer related deaths among women worldwide. The available evidence suggests that cardio-metabolic risk factors such as dyslipidemia and hypertension may contribute differently to breast cancer severity and pathogenesis. The aim of this study is to evaluate the interactive role of BC on dyslipidemia and HTN risk according to the type of treatment exposure and menopausal status.